Indonesia's Economic Impact of the Carbon Tax - Dani Ramdani (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2023)
What is the impact of the adoption of the carbon tax on climate change, carbon dioxide emissions, and other impacts on the Indonesian economy? is the research question raised in this paper. This study is crucial because although the Indonesian economy hasn't fully recovered, the government has announced plans to impose additional taxes that will burden businesses and industries and may lead to an increase in unemployment as a result of layoffs. This study was inspired by a number of studies on climate change and carbon dioxide emissions that show that, by 2050, the world will become hotter and more people would die from breathing poor air as a result of rising carbon dioxide emissions. The author tries to determine what effect a carbon price might have on Indonesia's economy. Data on the adoption of carbon taxes in 15 countries that have already done so was gathered by the authors between 1990 and 2019. This study adopted a descriptive qualitative methodology. The implementation of carbon taxes in several countries such as Finland and Sweden has proven successful in reducing carbon emissions and does not have a negative impact on their country's economy.